Home's Décor - Home Decoration Implementing Augmented Reality - Abdul Hamid, Mariam; Hamdan, Iskandar Zul Putera; Mustafa, Muhammad Amirul Asraf; Juliana Mohamed,; Mohamed Ali@Md Hani, Mohd Hatta; Ida Aryanie Bahrudin, (Multidisciplinary Applied Research and Innovation, 2021)
Abstract: Home’s Décor is a combination of Augmented Reality (AR) technology and interior design integrated into a smartphone application. The aim of this project is to present the implementation of an interior design mobile application using AR technology, a new alternative technology to projecting a virtual object into the real world with the device as an interface. The interior design application has the capability to project a three dimension (3D) object that can then be scaled, rotated and displaced by the user from multiple perspectives on a flat ground plane. This project was conducted by following the ADDIE Model while the project was designed and developed using Unity 3D and Vuforia. The Home Décor application prototype will widen the perspective of technology advancement where users can visualize the virtual world within the real world.